Analisis Metode Koordinasi Mata Dan Kaki Untuk Meningkatkan Kemampuan Menggiring Bola Pada Peserta Ekstrakurikuler Sepak Bola Di Smp Negeri 16 Satar Mese Tahun Ajaran 2025/2026 - Segi, Longginus; Ramli, Astuti Cendrawati; Derto, Ferderikus (CV. SINAR HOWUHOWU, 2026)
Problems seen from the results of the Pre-research, there are several factors that influence the ball dribbling skills of the extracurricular soccer participants of State Junior High School 16 Satar Mese with more male students participating with a total of 25 people, the ability and coordination of the eyes and feet, the ability to coordinate the eyes and feet when dribbling the ball in the extracurricular soccer participants of State Junior High School 16 Satar Mese still always look at the ball and have not been able to divert their attention from the direction of the ball. The data collection technique used in this study is the test technique, the test used in this study is a test of dribbling ability, and documentation when conducting research. Research data collection was carried out during extracurricular soccer activities at State Junior High School 16 Satar Mese. Processing can be done based on statistical methods in order to obtain a correct end or conclusion. So as to calculate the percentage of respondents. In the next step, data grouping was carried out based on the ability level category based on 5 criteria, namely: Very good, good, sufficient, less, very less and it can be concluded that eye and foot coordination has a significant role in improving dribbling ability, so that this coordination training method can continue to be developed in extracurricular football activities at SMP Negeri 16 Satar Mese.